ERCoRe Learning Model in Improving Students’ Critical Thinking Skills - Mustaqim Mustaqim; Aloysius Duran Corebima; Susriyati Mahanal (Jurnal Pendidikan Sains, 2019)
Abstract: Critical thinking skill is a skill in organizing and generating ideas, interpreting, analyzing, evaluating, and knowledge inference based on evidence, concept, criteria, methodology, or contextual consideration. Students’ critical thinking skill are still low and need to be improved. Critical thinking skill can be developed through student-centered learning. One of the learning models that can be used is ERCoRe learning model. This research aims to know the influence of ERCoRe learning model toward students’ critical thinking skill. The design of this research was quasi-experimental, conducted on senior high school students class. The data analysis that used was covariant. The conclusion based on the result’s of the analysis showed that there is the influence of ERCoRe learning model toward students’ critical thinking skill compared to conventional strategy. Key Words: critical thinking skills, ERCoRe learning modelAbstrak: Keterampilan berpikir kritis merupakan keterampilan seseorang dalam mengatur dan menghasilkan ide, menginterpretasi, menganalisis, mengevaluasi, dan menginferensi pengetahuan berdasarkan bukti, konsep, kriteria, metodologi, atau pertimbangan kontekstual yang sudah ada. Keterampilan berpikir kritis siswa pada umumnya masih rendah dan perlu ditingkatkan, di antaranya melalui penerapan kegiatan pembelajaran dimana siswa berperan aktif. Salah satunya model pembelajaran yang dapat digunakan adalah model pembelajaran ERCoRe. Penelitian bertujuan untuk melihat pengaruh model pem-belajaran ERCoRe terhadap keterampilan berpikir kritis siswa. Jenis penelitian adalah kuasi eksperimen, yang dilakukan pada sampel kelas siswa SMA. Analisis data menggunakan analisis kovarian dengan simpulan bahwa terdapat pengaruh model pembelajaran ERCoRe terhadap keterampilan berpikir kritis pada siswa dibandingkan dengan pembelajaran konvensional. Kata kunci: keterampilan berpikir kritis, model pembelajaran ERCoRe